Neuropsychological Status and Structural Brain Imaging in Adolescents With Single Ventricle Who Underwent the Fontan Procedure. Issue 12 (December 2015) - Bellinger, David C.; Watson, Christopher G.; Rivkin, Michael J.; Robertson, Richard L.; Roberts, Amy E.; Stopp, Christian; Dunbar‐Masterson, Carolyn; Bernson, Dana; DeMaso, David R.; Wypij, David; Newburger, Jane W.
Abstract : Background: Few studies have described the neuropsychological outcomes and frequency of structural brain or genetic abnormalities in adolescents with single ventricle who underwent the Fontan procedure. Methods and Results: In a cross‐sectional, single‐center study, we enrolled 156 subjects with single ventricle, mean age 14.5±2.9 years, who had undergone the Fontan procedure. Scores in the entire cohort on a standard battery of neuropsychological tests were compared with those of normative populations or to those of a group of 111 locally recruited healthy adolescents. They also underwent brain magnetic resonance imaging and were evaluated by a clinical geneticist. Genetic abnormalities were definite in 16 subjects (10%) and possible in 49 subjects (31%). Mean Full‐Scale IQ was 91.6±16.8, mean Reading Composite score was 91.9±17.2, and mean Mathematics Composite score was 92.0±22.9, each significantly lower than the population means of 100±15. Mean scores on other neuropsychological tests were similarly lower than population norms. In multivariable models, risk factors for worse neuropsychological outcomes were longer total support and circulatory arrest duration at first operation, presence of a genetic abnormality, more operations and operative complications, more catheterization complications, and seizure history. The frequency of any abnormality on magnetic resonance imaging was 11 times higher among Fontan adolescents than referents (66% versus 6%); 19 (13%) patients had evidence of a stroke, previously undiagnosed in 7 patients (40%). Conclusions: The neuropsychological deficits and high frequencies of structural brain abnormalities in adolescents who underwent the Fontan procedure highlight the need for research on interventions to improve the long‐term outcomes in this high‐risk group.